Nutrition composition of commercial full-fat and defatted black soldier fly larvae meal (Hermetia illucens) as a potential protein resource for aquafeeds - ISHAAQ SAPUTRA; YIH NIN LEE (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Saputra I, Lee YN. 2023. Nutrition composition of commercial full-fat and defatted black soldier fly larvae meal (Hermetia illucens) as a potential protein resource for aquafeeds. Biodiversitas 24: 4877-4884. Black Soldier Fly or BSF (Hermetia illucens) is one of the most researched insect species for its potential as a protein source in aquafeeds. In the present study, two commercially available full-fat and defatted BSF larvae were analyzed in terms of nutrition profiles including proximate composition, amino acids, fatty acids, and mineral contents. The defatted BSF was in the form of a meal and the full-fat BSF was in the form of overdried. The full-fat BSF larvae were ground using a food-grade milling machine and strained to obtain small particles. BSFL meals were then sent for laboratory analysis. Results indicated that the defatted BSFL have higher crude protein content than full-fat BSF, with crude protein value of 47.70% and 30.72%, respectively. In contrast, the crude lipid in the full-fat BSFL was 36.20%, higher than in defatted BSFL, with only 8.11% lipid content. The amino acids analysis indicated that only histidine was the amino acid that was higher in defatted BSF than in full-fat BSF. The availability of fatty acids in defatted BSFL was lower than in full-fat BSF. On the contrary, the Ca, Na, mg, Zn, Fe, Mn, and Cu in defatted BSF were higher than in the full-fat BSFL. In conclusion, full-fat and defatted BSF have comparable nutrition value to fishmeal sourced from bycatch fishes and the defatting process of BSFL improves the nutritional composition of BSFL including protein and amino acids. Therefore, it can be used as information for the correct choice of BSFL used in aquafeeds.